New humanism or posthumanism? Ethical and legal aspects of the legalisation of euthanasia in the world in the years 2000-2015 - Kobyliński, Andrzej (Studia Ecologiae et Bioethicae, 2020)
The main aim of this article is to outline the discussion on euthanasia that affects the basic aspects of human life – the foundation of human dignity, sense of pain and suffering, the conception of the afterlife, quality and value of life, etc. All the indications are that the process of the legalisation of euthanasia will develop in the coming decades. Today we need a new paradigm of bioethics, built on the basis of a new humanism, which will allow us to adequately analyse such phenomena as death, suffering and dying. The new paradigm of bioethics can be an effective tool in the dispute over the death on request.